Green Energy from Palm Kernel Shell Gasification – dual fuel engine performance analysis - Firman Asto Putro; Sunu Herwi Pranolo; Joko Waluyo; Dwi Hantoko; Agapeano Aditama; Mochamad Wahyu Utomo (Program studi Teknik Kimia UNS, 2024)
Electricity generation in Indonesia is mainly generated from non-renewable fuels. Based on these problems, this research utilizes palm kernel shells to be converted into producer gas as secondary fuel for a 5 kW diesel engine. Through a gasification process equipped with a cooling and gas cleaning system, low tar gas is fed to the diesel engine with variations of gas flow rate ratio to combustion air. A dummy load is installed to investigate the effect of load on diesel consumption. The diesel engine vibration increases due to using two fuel types was measured by installing a vibration meter. The research results show that the higher the load and the greater the ratio of producer gas injected, the less diesel consumption. At a gas ratio of 4:1 and an increase of load from 1 to 5 kW, the diesel fuel flow rate reduces by 25 - 31%. The most significant reduction in diesel consumption occurred at a load of 5 kW, valued at 38.49%. On the other hand, increasing the gas ratio causes an increase in diesel engine vibration. The research results showed an increase in engine vibration of 5.84% - 10.25%. The largest vibration was recorded at a load of 5 kW with a value of 92.4 m/s².Keywords:Gasification, Palm Kernel Shell, Dual Fuel Engine, Diesel Consumption, Diesel Engine Vibration